Thao - Lam, Thao (Owlkids Books, 2021)
""Thao" seems like a simple enough name. Only four letters--all of them belonging to many other names! And yet Thao had been called everything from "Tail" to "Theo" to "Towel." At one point, completely fed up, she decided it was time to try another name. Something "easy." Something like "Jennifer." But trying to be someone else only works for so long. And eventually "Jennifer" is swayed back to being herself when she opens her lunchbox and finds her mother has packed her Gỏi cuốn (also known as Vietnamese spring rolls)! Thao's favourite! Her name is pronounced "Tow" like the English word "how." While simple on the surface, this story of cultural assimilation and celebration of cultural pride runs deep. It is a personal one for Thao. And it will strike a chord with readers who have struggled to fit within a mainstream mold--then realized it was just more comfortable to be themselves. Visually, this book will also be a personal reflection of Thao in that she will be incorporating childhood photos into her usual cut-paper collage style! She has also opted to minimize the number of illustrations and instead play with type and typography as a way to highlight her name--and the many variations of it that appear in the book!"--